Life-Threatening Complications of Influenza vs Coronavirus Disease 2019 (COVID-19) in US Children. (15th July 2022) - Halasa, Natasha B; Spieker, Andrew J; Young, Cameron C; Olson, Samantha M; Newhams, Margaret M; Amarin, Justin Z; Moffitt, Kristin L; Nakamura, Mari M; Levy, Emily R; Soma, Vijaya L; Talj, Rana; Weiss, Scott L; et al.
Abstract: Background: Clinical differences between critical illness from influenza infection vs coronavirus disease 2019 (COVID-19) have not been well characterized in pediatric patients. Methods: We compared demographics, clinical characteristics, and outcomes of US children (aged 8 months to 17 years) admitted to the intensive care or high-acuity unit with influenza or COVID-19. Using mixed-effects models, we assessed the odds of death or requiring life support for influenza vs COVID-19 after adjustment for age, sex, race and Hispanic origin, and underlying conditions including obesity. Results: Children with influenza (n = 179) were younger than those with COVID-19 (n = 381; median, 5.2 years vs 13.8 years), less likely to be non-Hispanic Black (14.5% vs 27.6%) or Hispanic (24.0% vs 36.2%), and less likely to have ≥1 underlying condition (66.4% vs 78.5%) or be obese (21.4% vs 42.2%), and a shorter hospital stay (median, 5 days vs 7 days). They were similarly likely to require invasive mechanical ventilation (both 30.2%), vasopressor support (19.6% and 19.9%), or extracorporeal membrane oxygenation (2.2% and 2.9%). Four children with influenza (2.2%) and 11 children with COVID-19 (2.9%) died. The odds of death or requiring life support in children with influenza vs COVID-19 were similar (adjusted odds ratio, 1.30; 95% confidence interval, .78–2.15; P = .32). Conclusions: Despite differences in demographics and clinical characteristics of children with influenza or COVID-19, the frequency of life-threatening complications was similar. Our findings highlight the importance of implementing prevention measures to reduce transmission and disease severity of influenza and COVID-19. Abstract : Our multicenter comparison of severe pediatric influenza to severe coronavirus disease 2019 demonstrated similar frequencies of life-threatening complications. However, children with influenza critical illness were younger and more often previously healthy. Effective vaccination against influenza and severe acute respiratory syndrome coronavirus 2 is essential for child health.